(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Despite existing literature that demonstrates the relation between anattitude of social responsibility and activism; few studies have examined theunderlying factor structure of social responsibility. The current study had twogoals. The first goal was to examine the structure of a measure of socialresponsibility attitude for urban adolescents. The second goal was to examinethe associations of social responsibility with civic and political activism.Confirmatory factor analysis of social responsibility items revealed that amodel with a single latent factor explained the data better than a two-factormodel with one latent factor representing neighborhood social responsibilityand the other representing global social responsibility. There were significantpositive relations between social responsibility and civic activism andpolitical activism when controlling for parental activism and peer activism.This study suggests that a social responsibility attitude may exist as a singlefactor amongst urban adolescents and it has added empirical support to showthat higher levels of social responsibility are associated with greater depthof involvement in civic and political activism. Implications for both theoryand practice are discussed.